Processing Cow's Milk into Milk Pudding as an Effort to Improve the Economy Of The Community in Kemiri Village, Puspo Sub-District, Pasuruan District - Abdurrahman, Abdurrahman; Ningsih, Indah Rahayu Dwi; Setiawan, Risqi Firdaus (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2025)
Milk pudding-making training is one of the solutions to improve the skills of the Kemiri Village community in processing fresh cow's milk into value-added products, especially milk pudding. The method employed was a two-day interactive training session involving groups of mothers in the village, where participants were taught pudding-making techniques, the selection of high-quality ingredients, and marketing strategies. The results of the training showed an increase in the community's knowledge and skills in processing milk, which has the potential to increase their income. This study concludes that through this training, the community can not only optimally utilise local resources but also create new, sustainable business opportunities and improve the economic welfare of families in Kemiri Village. Contribution to Sustainable Development Goals (SDGs):SDG 1: No Poverty SDG 2: Zero HungerSDG 5: Gender EqualitySDG 8: Decent Work and Economic GrowthSDG 12: Responsible Consumption and ProductionSDG 17: Partnerships for the Goals